ANALISIS PARAMETER NETWORK SENTRAL NEAX 61EDI PT. TELKOM LHOKSEUMAWE - - Nasri (Politeknik Negeri Lhokseumawe, 2014)
The main objective of this study was to determine the quality of the communication path or circuit switching networks in Central Phone type NEAX 61E in PT. Telkom Lhokseumawe by analyzing traffic data and from 1 January to December, 2011 . The research method was performed by taking the data and observing the data of the central type . Observations were carried out by using the parameters MHTS (Mean Holding Time Per Seizure) , SCH (Seizure per circuit per hour) , GoS (Grade of Service), OCC (Occupancy Circuit), and ASR (Answered Seizure Ratio). The results showed that in February links Banda Aceh had 285.4 minutes at a density of 1.5 calls Call/circuits . Seizure per circuit hour (SCH) with the highest number of calls reached 12.9 1.65794 million calls. Hence, lower SCH would provide insufficient circuit,. Standards set by PT. Telkom did not exceed 24 call/circuit and effectiveness of call in the circuit should not be more than 2 minutes, so the conditions provided by the PT. Telkom is not good because of the density and the call do not occur with a low MHTS